Saponins and their role as vaccine adjuvant against coccidiosis in poultry - Abdullah F. ALSAYEQH (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Coccidiosis, induced by various Eimeria species, has been one of the most important health threats and performance of poultry around the world. Other than the current treatment, successful vaccination approaches have been realized. Advances in saponin biochemistry, from Quillaja saponaria and Yucca schidigera plants, have supported the development of vaccine adjuvants based on these natural glycosides. Saponins also activate innate immune pathways and can assist with antigen presentation, enhancing humoral and cell-mediated responses. Saponin-based adjuvants, including QS-21 and Quil A, can enhance adjuvant efficacy by inducing higher antibody responses and promoting long-lasting protective immunity privation. Nonetheless, challenges including toxicity issues about the saponin fractions and the variable adjuvant activity among different saponins, have also been reported. Future studies aim to improve saponin adjuvant formulations, determine their harmlessness, and investigate new transport systems, such as immunostimulating complexes. By enhancing poultry health, such advancements contribute to safer meat and egg products, directly supporting food safety. Moreover, reducing disease-related losses in poultry farms promotes food security by ensuring stable and efficient protein production. The focus of this review article is to highlight the role of saponins as vaccine adjuvants to enhance immunity against Eimeria species in poultry.